Direct Patterning of Ionic Polymers with E-Beam Lithography. Issue 1 (2016) - Steinbach, Annina M.; Jenisch, Stefan; Bakhtiarpour, Parisa; Amirkhani, Masoud; Strehle, Steffen
ABSTRACT: Controlling the bending properties of ionic polymer-metal composites may immediately affect their implementation in robotics and medicine. In the present work, we propose a direct patterning method for the ionic polymer Nafion using conventional electron-beam writing. In a proof-of-concept study, we show that patterns of arbitrary geometry and sizes between 1 µm and 50 µm can be engraved into the polymer surface without using resists. Pattern depth can be deliberately controlled by adjusting the exposure dose. The patterns were stable even after prolonged immersion in ionic solution. The presented technique therefore opens up the possibility to create unique electrode geometries and to investigate independently the effect of pattern size, density, depth as well as geometry on ionic polymer-metal composite bending.